Performing lower-limb strength exercises before or after training does not influence fatigue indices in competitive youth soccer players - Gantzer, C.; Huff, D.; Butterick, B.; Chalmers, S.; Marshall, P.; Lovell, R.; Siegler, J. C. (The Journal of Strength and Conditioning Research, 2024)
A multicenter approach was used to conduct a controlled, laboratory-based study (Part A) in conjunction with an ecologically focused, field-based study (Part B) of the influence of timing on hamstring fatigue induced by lower-limb strength exercises. Part A required players to perform the FIFA 11+ warm-up before a simulated soccer training session, whereas the other session involved removing the lower-limb strength exercises from the warm-up and delivering them after the simulated session. For Part B, players completed 2 live training sessions, where one session included the Nordic hamstring exercise (NHE) as part of a standardized warm-up before training and the other session incorporated the NHE at the end of training. Maximal hamstring force (MVC), rate of force development (RFD), countermovement jump (CMJ), and sprint speed (SS) were assessed before, during, and after the simulation and field training, respectively, to quantify fatigue across both study cohorts. There was no suggestion that timing of the intervention had an influence fatigue in either Part A or B, with no condition (MVC [Part A & B]: p > 0.43; RFD: p = 0.43; CMJ: p = 0.10; SS: p = 0.62), time (MVC: p > 0.30; RFD: p = 0.72; CMJ: p = 0.87; SS: p = 0.85), or interactions (MVC: p > 0.93; RFD: p = 0.78; CMJ: p = 0.99; SS: p = 0.94) evident. Our findings suggest youth soccer coaches should not be concerned with the timing of interventions, allowing them to focus instead on adherence and player buy-in.